Evaluation of the Implementation of (SSOP) and (GMP) in the Amplang Mackerel Fish Business in Pemangkat District, Sambas Regency - Saifudin, Saifudin; Suprianto, Suprianto; Hanavi, Muhammad Ilham; Mogi, Gabriela; Hesti, Hesti; Agam, Beryaldi; Mahyudi, Indra (Journal of Fisheries and Marine Applied Science, 2024)
This study aimed to evaluate the implementation of Sanitation Standard Operating Procedures (SSOP) and Good Manufacturing Practices (GMP) in the mackerel fish amplang business in Pemangkat District, Sambas Regency. The evaluation was conducted through direct observation and interviews using a checklist based on SSOP and GMP guidelines. Results showed that the implementation of SSOP and GMP was not yet optimal, with several non-conformities, particularly in aspects of production location and environment, building and facilities, production equipment, hygiene and sanitation facilities, employee hygiene, storage, food labeling, supervision, and employee training. However, some aspects were satisfactory, such as clean water supply, chemical handling, hygiene and sanitation programs, pest control, waste management, process control, product recall, and recording and documentation. Improvements in various aspects are needed to meet food safety standards and ensure product quality. This study recommends enhancing SSOP and GMP implementation to ensure the safety and quality of mackerel fish amplang products. Additionally, the application of cleaner production principles using the 1E4R strategy (Elimination, Reduce, Reuse, Recycle, Recovery) or 5R (Re-think, Re-use, Reduction, Recovery, Recycle) is suggested to prevent and reduce waste, with primary emphasis on prevention and reduction strategies.